Porous membrane as well as preparation method and application thereof
By controlling the projection area of the projection part during laser drilling and filling the solid electrolyte, the problems of uneven surface of the porous membrane and internal stress are solved, the mechanical strength and battery performance of lithium-ion batteries are improved, and the impedance and short-circuit rate are reduced. .
Patent Information
- Application Number
- CN202411246123.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-13
AI Technical Summary
The protrusions formed by the porous membrane of existing solid-state lithium-ion batteries during laser drilling lead to uneven surfaces, increasing thickness and internal stress, reducing mechanical strength, and affecting the mass energy density and safety performance of the battery.
By controlling the ratio of the total projected area of the projected area of the protruding portion formed during laser drilling on the membrane surface to the area of the membrane surface, it is carried out within a specific range by combining the pulse output energy, repetition frequency and membrane surface operation speed of the CO2 laser The hole punching process forms a porous film with high mechanical strength and a flat surface, and fills the pores with solid electrolytes.
The high mechanical strength and flat surface of the porous membrane are achieved, the impedance and short-circuit rate of the battery are reduced, the mass energy density and safety performance of the battery are improved, and the negative impact of the increase in the battery thickness on the energy density is avoided.
Smart Images

Figure CN119115269A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials and relates to a porous membrane and a preparation method and application thereof. Background Art
[0002] Commercial lithium-ion batteries currently mainly use organic liquid electrolytes. However, due to the characteristics of organic solvents being flammable, easy to leak, and easy to volatilize, there are potential risks such as battery overcharging and short circuits, which make liquid organic electrolyte lithium-ion batteries have certain safety hazards in use. All-solid-state lithium batteries are expected to solve safety problems such as electrolyte leakage, combustion, and short circuits caused by lithium dendrites piercing the diaphragm in liquid lithium batteries.
[0003] The current mainstream solid electrolyte membrane is usually obtained by punching holes in the film. Laser drilling is a relatively efficient drilling method. It uses a high-power density laser beam to irradiate the processed material. The spot irradiation area quickly heats up, melts and vaporizes, producing straight holes of a certain diameter, thereby forming a porous membrane. However, the molten polymer produced during the punching process will accumulate on the surface of the film around the hole, forming a significant crater shape, making the surface of the porous membrane uneven, significantly increasing the thickness of the porous membrane and reducing the mass energy density of the battery. The uneven surface causes uneven internal stress distribution on the surface of the porous membrane, which reduces the mechanical strength of the porous membrane and makes it difficult to apply to the coating and assembly process of the battery. Summary of the invention
[0004] The present invention provides a porous membrane and a preparation method and application thereof. The porous membrane provided by the present invention can prevent a significant increase in the thickness of the porous membrane and maintain a relatively uniform internal stress distribution on the surface of the porous membrane by controlling the ratio of the total projected area of convex parts formed in the laser drilling process on the membrane surface of the porous membrane to the membrane surface area of the porous membrane to be ≤80% and not 0, so that the porous membrane has higher mechanical strength and enables the battery to maintain higher mass energy density, lower impedance and lower short circuit rate when applied to the battery.
[0005] A first aspect of the present invention provides a porous membrane formed by laser drilling, wherein the porous membrane comprises a plurality of through holes and protrusions distributed around the through holes, wherein the protrusions protrude from the membrane surface of the porous membrane;
[0006] The ratio of the total projected area of the protrusions on the surface of the porous membrane to the surface area of the porous membrane is ≤80% and is not 0.
[0007] In the porous membrane as described above, the ratio of the total projected area of the protrusions on the membrane surface of the porous membrane to the membrane surface area of the porous membrane is 18% to 70%.
[0008] In the porous membrane as described above, the through hole is circular in shape, the projection of the protrusion on the surface of the porous membrane is a circular ring, and the ratio of the width of the circular ring to the outer circle radius is ≤75%.
[0009] The porous membrane as described above, wherein the ratio of the height of the protrusion to the thickness of the porous membrane is ≤50%;
[0010] And / or, the porous membrane has a thickness of 5 μm to 20 μm.
[0011] The porous membrane as described above, wherein the porosity of the porous membrane is ≥12%, and the ratio of the total projected area of the protrusions on the membrane surface of the porous membrane to the membrane surface area of the porous membrane is ≤70%.
[0012] A second aspect of the present invention provides a method for preparing the porous membrane as described above, comprising the following steps:
[0013] The base film is subjected to laser drilling treatment by using a laser drilling device to obtain the porous film;
[0014] The laser drilling process meets the following conditions: the laser scanning speed is 10 mm / s to 200 mm / s, the pulse output energy is 5.4 W to 9 W, the pulse repetition frequency is 8 kHz to 100 kHz, and the pulse width is 0.1 ms to 0.7 ms.
[0015] In the preparation method as described above, the laser drilling device is selected from a CO2 laser.
[0016] The preparation method as described above, wherein, before the laser drilling process is performed, the base film is further subjected to a cooling process so that the temperature of the base film surface is ≤0°C;
[0017] And / or, before performing the laser drilling process, the method further includes drying the environment in which the laser drilling device is located to reduce the humidity of the environment to below the dew point temperature.
[0018] A third aspect of the present invention provides an electrolyte membrane, comprising the porous membrane as described above and a solid electrolyte filled in the pores of the porous membrane.
[0019] A fourth aspect of the present invention provides a battery comprising the electrolyte membrane as described above.
[0020] The implementation of the present invention has at least the following advantages:
[0021] 1) The porous membrane provided by the present invention can maintain a relatively uniform internal stress distribution on the surface of the porous membrane without significantly increasing the thickness of the porous membrane by controlling the ratio of the total projected area of the protrusions formed during the laser drilling process on the surface of the porous membrane to the surface area of the porous membrane ≤80%, so that the porous membrane has a higher mechanical strength and maintains a higher mass energy density of the battery when applied to the battery. Controlling the above ratio not to be 0 is conducive to using the protrusions to load more solid electrolytes on the surface of the porous membrane, thereby exerting the lithium ion conduction effect and reducing the battery impedance. At the same time, the above ratio ≤80% can also avoid the pore size on the surface of the porous membrane being too large, making the pore tortuosity of the porous membrane relatively low and difficult to effectively play the role of isolating the positive and negative electrodes, thereby avoiding the occurrence of battery short circuit.
[0022] 2) The method for preparing the porous membrane provided by the present invention can reasonably control the accumulation of the molten polymer during the laser drilling process by controlling the membrane surface running speed, pulse output energy, pulse repetition frequency, and pulse width during the laser drilling process within a specific range, so that the ratio of the total projected area of the protrusions formed during the drilling process on the membrane surface of the porous membrane to the membrane surface area of the porous membrane is ≤80% and not 0, thereby obtaining a porous membrane with a relatively smooth membrane surface, a relatively uniform surface internal stress distribution, and the ability to load a certain amount of solid electrolyte.
[0023] 3) The electrolyte membrane provided by the present invention comprises the above-mentioned porous membrane and the solid electrolyte filled in the pores of the porous membrane. The high film surface flatness and mechanical strength of the porous membrane itself can also make the electrolyte membrane have higher safety performance during application, and can also avoid the increase of battery thickness, reducing the negative impact on battery energy density. In addition, by filling the solid electrolyte in the porous membrane, the straight-through property of the hole can be reduced, the probability of battery short circuit can be reduced, and compared with the traditional diaphragm with only a solid electrolyte layer coated on the surface of the base film, the solid electrolyte is filled in the pores of the porous membrane. The channel tortuosity of the straight-through hole can be increased, and then it has a lower permeability value and better ion conduction characteristics, which is conducive to the transmission of lithium ions, and can improve the rate performance of the battery, reduce the impedance of the battery and the short circuit rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is a SEM image of a porous membrane formed by laser drilling;
[0025] Figure 2 Schematic diagram of a porous membrane preparation process according to an embodiment of the present invention.
[0026] Description of reference numerals:
[0027] 1-base film; 2-through hole; 3-laser. DETAILED DESCRIPTION
[0028] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Figure 1 is a SEM image of a porous membrane formed by laser drilling. Figure 1 As shown, due to the significant thermal effect of the laser, the molten material produced during the punching process accumulates on the surface of the film around the straight-through hole to form a convex portion, making the surface of the porous membrane uneven, significantly increasing the overall thickness of the porous membrane and reducing the mass energy density of the battery. The uneven surface causes uneven internal stress distribution on the surface of the porous membrane, which reduces the mechanical strength of the porous membrane.
[0030] Based on this, the first aspect of the present invention provides a porous membrane formed by laser drilling, wherein the porous membrane comprises a plurality of through holes and protrusions distributed around the through holes, wherein the protrusions protrude from the membrane surface of the porous membrane;
[0031] The ratio of the total projected area of the protrusions on the membrane surface of the porous membrane to the membrane surface area of the porous membrane is ≤80% and is not 0.
[0032] In the present invention, “several” means that the present invention does not impose a specific limitation on the number of through holes, which may be one or more, and the specific number may be determined according to different porosity requirements.
[0033] "Through holes" refer to holes that pass through the upper and lower surfaces of the porous membrane. Since the through holes are formed by laser drilling, the molten polymer generated during the drilling process will not only accumulate on the upper surface of the porous membrane, but also on the lower surface of the porous membrane. Therefore, the upper and lower surfaces of the porous membrane both include protrusions distributed on the periphery of the through holes.
[0034] The "membrane surface" includes the upper and lower surfaces of the porous membrane, wherein the surface of the protrusion and the location of the through hole do not belong to the scope of the membrane surface. For example, when the porous membrane is rectangular, its membrane surface area can be obtained by subtracting the sum of the areas of the through hole and the protrusion from the product of the length and the width.
[0035] The present invention has been found that by controlling the ratio of the total projected area of the protrusions on the porous membrane surface to the membrane surface area of the porous membrane to be ≤80% and not 0, wherein the ratio of the total projected area of the protrusions on the porous membrane surface to the membrane surface area of the porous membrane is ≤80%, the thickness of the porous membrane can be kept unchanged and a relatively uniform internal stress distribution on the surface of the porous membrane can be maintained, so that the porous membrane has a higher mechanical strength and the battery maintains a higher mass energy density when applied to a battery. Controlling the above ratio to be not 0 is conducive to utilizing the above protrusions to load a solid electrolyte on the surface of the porous membrane, thereby exerting a lithium ion conduction effect and reducing the battery impedance. At the same time, the above ratio of ≤80% can also avoid the pore size on the surface of the porous membrane being too large, making the pore tortuosity of the porous membrane relatively low and difficult to effectively play the role of isolating the positive and negative electrodes, thereby avoiding the occurrence of battery short circuit.
[0036] In a preferred embodiment, the ratio of the total projected area of the protrusions on the surface of the porous membrane to the surface area of the porous membrane is 18% to 70%. It is understandable that if the proportion of the protrusions on the surface of the porous membrane is too large, the fit between the porous membrane and the pole piece will deteriorate, and the battery interface impedance will increase; if the proportion of the protrusions on the surface of the porous membrane is too small, it will not be conducive to loading more solid electrolytes, nor will it be conducive to improving the battery impedance. Within the above ratio range, it is conducive to balancing the improvement effect of the solid electrolyte load on the impedance and the disadvantages caused by the poor fit between the composite membrane and the pole piece, so that the battery has a higher impedance performance.
[0037] In a preferred embodiment, the through hole is in the shape of a circle, and the projection shape of the protrusion on the porous membrane surface is a ring, and the ratio of the width of the ring to the outer radius is ≤75%. Exemplary, the ratio of the width of the ring to the outer radius can be 75%, 60%, 50%, 40%, 35%, 25% or the range composed of any two of the above values. Compared with holes of other shapes, circular holes are more uniformly stressed in all directions, and are not prone to tearing, cracking, etc. in a certain direction. In addition, the ratio of the width of the ring to the outer radius is ≤75%, which is conducive to reducing the amplitude effect of the protrusion on the overall strength of the membrane. If it exceeds 75%, the overall strength of the membrane will be significantly reduced, and the spacing and size between the holes are not easy to be controlled.
[0038] It is worth mentioning that when the shape of the through hole is not a regular circular shape, but a shape that is approximately circular, such as a rounded polygon, the above characteristics can also be met so that the stress of the through hole in all directions is more uniform, and it is not easy to tear or crack in a certain direction.
[0039] In a preferred embodiment, the ratio of the height of the protrusion to the thickness of the porous membrane is ≤50%. Exemplarily, the ratio of the height of the protrusion to the thickness of the porous membrane can be 50%, 45%, 40%, 35%, 30%, 25%, 20%, 15%, 10%, 5% or a range consisting of any two of the above values. It is understood that when applied to a battery, controlling the ratio of the height of the protrusion to the thickness of the porous membrane within the above range is conducive to avoiding excessive increase in battery thickness and further improving the energy density of the battery.
[0040] The shape, height, area and other parameters of the protrusion of the present invention can be obtained by fitting and calculating the scanning electron microscope image with image processing software.
[0041] In a specific embodiment, the thickness of the porous membrane is 5 μm to 20 μm. Exemplarily, the thickness of the porous membrane can be 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm or a range consisting of any two of the above values. The porous membrane in the above thickness range is applied to lithium-ion batteries to avoid the mechanical strength of the electrolyte membrane being affected by too small a thickness, and to avoid the energy density of the battery being affected by too large a thickness.
[0042] In a preferred embodiment, the porosity of the porous membrane is ≥12%, and the ratio of the total projected area of the protrusions on the surface of the porous membrane to the surface area of the porous membrane is ≤70%. The greater the porosity of the porous membrane, the better the air permeability of the electrolyte membrane, and it can also reduce the migration resistance of lithium ions therein, which is beneficial to reducing the internal resistance of the battery. However, it is understandable that the greater the porosity, the more through holes there are in the porous membrane, and accordingly, more protrusions are more likely to be produced during the laser drilling process. Therefore, the present application controls the total projected area of the protrusions on the surface of the porous membrane to account for ≤70% of the surface area of the porous membrane while making the porosity of the porous membrane ≥12%. While the porous membrane maintains good air permeability, it also makes the membrane surface have a lower roughness, maintains good mechanical strength, and is more conducive to the subsequent assembly of the battery.
[0043] In a specific embodiment, the aperture of the through hole is 1 to 50 μm. Exemplarily, the aperture of the through hole can be 1 μm, 3 μm, 5 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm or a range consisting of any two of the above values. It is understandable that if the aperture of the through hole is too small, the transmission speed of lithium ions will be affected, and if the aperture of the through hole is too large, it is easy to cause a short circuit in the battery.
[0044] The present invention does not specifically limit the material of the porous membrane, but preferably a polymer membrane with high heat resistance can form a molten polymer with less content during laser drilling, and can also enable the battery to obtain higher thermal safety performance when applied to the battery. In a specific embodiment, the material of the porous membrane includes but is not limited to one or more of polyethylene terephthalate (PET), polyimide (PI), polybutylene terephthalate (PBT), polyethylene naphthalate (PEN), polyetheretherketone (PEEK), polyphenylene sulfide (PPS), and polybenzimidazole (PBI).
[0045] In order to optimize the performance or further increase the porosity of the finished membrane, high temperature resistant, high strength porous or fibrous membrane substrates can also be used, such as cellulose nonwoven fabrics, PET fiber nonwoven fabrics, PI electrospun fiber membranes, aramid electrospun fiber membranes, etc.
[0046] A second aspect of the present invention provides a method for preparing a porous membrane, comprising the following steps:
[0047] The base film is subjected to laser drilling treatment by using a laser drilling device to obtain a porous film;
[0048] Among them, the laser drilling process meets the following conditions: the film surface moving speed is 10mm / s~200mm / s, the pulse output energy is 5.4W~9W, the pulse repetition frequency is 8kHz~100kHz, and the pulse width is 0.1ms~0.7ms.
[0049] Figure 2 FIG. 1 is a schematic diagram of a porous membrane preparation process according to an embodiment of the present invention. Figure 1 As shown, the laser 3 emits laser light to irradiate the base film 1, and the irradiated area generates a thermal effect and melts to form a through hole 2. The position of the laser 3 can be fixed and the base film can be moved to form through holes in different areas of the base film.
[0050] The base film can be either a porous film with a certain pore structure or a non-porous film. CO2 laser (wavelength 10.64 μm) is a laser in the infrared light band, which has a stronger thermal effect and can achieve efficient drilling.
[0051] The film surface running speed refers to the speed at which the base film moves during the laser drilling process. Usually, the position of the laser is kept unchanged during the drilling process, and the laser scanning speed is controlled by controlling the moving speed of the base film. For example, the laser drilling device can be used in conjunction with a film roll traction device, the film roll traction device is used to move the base film, and the film roll migration device is controlled to run intermittently. When the base film moves, the laser is suspended from irradiating the laser, and when the base film stops, the laser is turned on to irradiate the laser for drilling.
[0052] Pulse output energy refers to the energy of a single laser pulse output by the laser. The greater the pulse output energy, the stronger the heating effect of a single pulse on the material and the higher the temperature of the base film surface. However, too high pulse output energy can cause deformation, cracks, pores and other defects in the base film.
[0053] The pulse repetition frequency refers to the number of times or pulses emitted by the laser per unit time. A higher pulse repetition frequency is beneficial to improving processing speed and efficiency, but when the pulse repetition frequency is too high, it will be detrimental to processing accuracy, making it difficult to control the area of the raised part.
[0054] Pulse width refers to the period during which the pulse can reach its maximum value. When the pulse energy remains unchanged, the peak value is inversely proportional to the pulse width. The shorter the pulse width, the greater the time energy density of the laser, and the stronger the effect of the laser on the basement membrane. Conversely, the weaker the effect of the laser on the tissue. The change of pulse width has a greater impact on the aperture.
[0055] The inventors have found that by controlling the membrane surface running speed, pulse output energy, pulse repetition frequency and pulse width during the laser drilling process within the above ranges, the amount and distribution morphology of the molten polymer generated around the holes during the drilling process can be effectively controlled to obtain the porous membrane defined in the first aspect above.
[0056] In addition to the above-mentioned pulsed laser, the present invention can also use a continuous laser to complete the laser drilling process. However, the continuous laser needs to be intermittently powered off and restarted to obtain spaced holes, and the processing efficiency is low.
[0057] Furthermore, the laser drilling device is selected from a CO2 laser, which has a strong thermal effect, matches the above-mentioned drilling conditions, and can achieve accurate and efficient drilling.
[0058] In a preferred embodiment, before the laser drilling process, the base film is further cooled to make the temperature of the base film surface ≤ 0° C. Cooling the base film can better control the structure of the holes and avoid the generation of microcracks.
[0059] The present invention does not specifically limit the cooling method of the base film. For example, the base film may be cooled by a low-temperature cold roller, low-temperature air, liquid nitrogen, or liquid carbon dioxide.
[0060] In another preferred embodiment, before the laser drilling process is performed, the environment in which the laser drilling device is located is dried to reduce the humidity of the environment to below the dew point temperature.
[0061] If the ambient humidity is too high, water droplets will form on the membrane surface, which will refract or scatter the laser, resulting in poor consistency of the holes formed by the processing. By reducing the ambient humidity to below the dew point temperature, significant condensation water on the base membrane surface can be avoided, thereby avoiding the above adverse effects.
[0062] The third aspect of the present invention provides an electrolyte membrane, comprising a porous membrane provided by the first aspect of the present invention and a solid electrolyte filled in the pores of the porous membrane. The high film surface flatness and mechanical strength of the porous membrane itself can also enable the electrolyte membrane to have higher safety performance during application, and can also avoid the increase in battery thickness, reducing the negative impact on battery energy density. In addition, by filling the porous membrane with a solid electrolyte, the directness of the pores can be reduced, reducing the probability of battery short circuit, and compared to the traditional diaphragm with only a solid electrolyte layer coated on the surface of the base film, filling the solid electrolyte in the pores of the porous membrane can increase the channel tortuosity of the straight-through hole, thereby having a lower permeability value and better ion conduction characteristics, which is conducive to the transmission of lithium ions, and can improve the rate performance of the battery and maintain a low impedance.
[0063] The present invention does not specifically limit the type of the above-mentioned solid electrolyte, which can be selected from solid electrolytes conventionally used in the art, including but not limited to one or more of oxide solid electrolytes, polymer solid electrolytes, sulfide solid electrolytes, and gel electrolytes. Among them, the oxide solid electrolyte is preferably aluminum titanium phosphate (LATP) or lithium lanthanum zirconium oxide (LLZO), the polymer solid electrolyte is preferably copolymer-modified polyethylene oxide (PEO), and the sulfide solid electrolyte is preferably Li6PS5Cl.
[0064] In a specific embodiment, the electrolyte membrane comprising a porous membrane and a solid electrolyte filled in the pores of the porous membrane can be prepared by the following method:
[0065] The solid electrolyte is made into slurry and then coated on the porous membrane, and then dried and solidified to obtain the electrolyte membrane.
[0066] The coating method can be selected from one or more of screen roller coating, wire rod coating, dip coating and extrusion coating; the drying temperature is preferably 60-80°C.
[0067] The fourth aspect of the present invention provides a battery, comprising the electrolyte membrane provided by the third aspect of the present invention. Since the electrolyte membrane has relatively good membrane surface flatness, high mechanical strength, low air permeability and good ion conductivity, the battery has a low internal impedance while maintaining a high energy density, so that the battery has a high rate performance.
[0068] The battery of the present invention may be a liquid battery, a solid-state battery, or a semi-solid-state battery, and more preferably a solid-state battery or a semi-solid-state battery. In addition to the above-mentioned electrolyte membrane, the battery of the present invention further comprises a positive electrode sheet, a negative electrode sheet, and an electrolyte, wherein the positive electrode sheet, the negative electrode sheet, and the electrolyte may all refer to the positive electrode sheet, the negative electrode sheet, and the electrolyte conventionally used in lithium-ion batteries, and will not be described in detail here.
[0069] The porous membrane provided by the present invention and its preparation method and application will be further described in detail below through specific examples. Obviously, the following examples are only some embodiments of the present invention, not all embodiments. Based on the technical solutions and given embodiments provided by the present application, all other embodiments obtained by those skilled in the art without creative work are within the protection scope of the present invention.
[0070] The CO2 laser used in the following examples and comparative examples is from Shenzhen Dapeng Laser Technology Co., Ltd. The laser wavelength of the CO2 laser is 10.64 μm and the maximum pulse energy is 60 W.
[0071] Example 1
[0072] This embodiment provides a porous membrane, and the preparation method thereof comprises the following steps:
[0073] 1) A biaxially oriented PET film with a thickness of 10 μm was used as the base film, and liquid carbon dioxide was used to cool the base film so that the temperature of the base film surface was lower than 0°C. At the same time, dry nitrogen was introduced into the laser punching area to reduce the ambient humidity to below the dew point.
[0074] 2) using a CO2 laser to punch holes in the base film to obtain a porous film;
[0075] The control parameters of the punching process are: pulse energy output 9% (5.4 W), repetition frequency 80 kHz, pulse width 0.1 ms, and membrane surface running speed 100 mm / s.
[0076] Example 2
[0077] This embodiment provides a porous membrane, and the preparation method thereof comprises the following steps:
[0078] A PET film with a thickness of 10 μm was used as the base film, and a CO2 laser was used to punch holes therein to obtain a porous film;
[0079] The control parameters of the punching process are: membrane surface running speed 100 mm / s, pulse energy output 15% (9 W), repetition frequency 50 kHz, and pulse width 0.7 ms.
[0080] Example 3
[0081] This embodiment provides a porous membrane, and its preparation method is basically the same as that of embodiment 1, except that the pulse energy output is adjusted to 12% (7.2 W).
[0082] Example 4
[0083] This embodiment provides a porous membrane, and its preparation method is basically the same as that of Example 1, except that the membrane surface running speed is adjusted to 50 mm / s, the pulse energy output is adjusted to 15% (9 W), the repetition frequency is adjusted to 50 kHz, and the pulse width is adjusted to 0.7 ms.
[0084] Example 5
[0085] This embodiment provides a porous membrane, and its preparation method is basically the same as that of Embodiment 1, except that the base membrane is replaced with a PET non-woven fabric with a thickness of 10 μm.
[0086] Example 6
[0087] This embodiment provides a porous membrane, and its preparation method is basically the same as that of Embodiment 1, except that the base membrane is replaced by a PBT membrane with a thickness of 10 μm.
[0088] Example 7
[0089] This embodiment provides a porous membrane, and its preparation method is basically the same as that of Embodiment 1, except that the base membrane is replaced by a PI membrane with a thickness of 10 μm.
[0090] Example 8
[0091] This embodiment provides a porous membrane, and the preparation method thereof comprises the following steps:
[0092] A PET film with a thickness of 22 μm was used as the base film, and a CO2 laser was used to punch holes therein to obtain a porous film;
[0093] The control parameters of the punching process are: membrane surface running speed 150 mm / s, pulse energy output 15% (9 W), repetition frequency 30 kHz, and pulse width 0.1 ms.
[0094] Example 9
[0095] This embodiment provides a porous membrane, and its preparation method is basically the same as that of Example 8, except that the membrane surface running speed is 120 mm / s.
[0096] Example 10
[0097] This embodiment provides a porous membrane, and its preparation method is different from that of embodiment 1 in that the control parameters of the punching process are: membrane surface running speed 30 mm / s, pulse energy output 15% (9W), repetition frequency 80 kHz, and pulse width 0.7 ms.
[0098] Comparative Example 1
[0099] This comparative example provides a porous membrane, and its preparation method is basically the same as that of Example 2, except that the membrane surface running speed is adjusted to 10 mm / s, the pulse energy output is adjusted to 18% (10.8 W), the repetition frequency is adjusted to 80 kHz, and the pulse width is adjusted to 0.8 ms.
[0100] Comparative Example 2
[0101] This comparative example provides a porous membrane, and its preparation method is basically the same as that of comparative example 1, except that the membrane surface running speed is adjusted to 15 mm / s, the pulse energy output is adjusted to 15% (9 W), the repetition frequency is adjusted to 120 kHz, and the pulse width is adjusted to 0.1 ms.
[0102] Comparative Example 3
[0103] This comparative example provides a porous membrane, and its preparation method is basically the same as that of comparative example 1, except that the membrane surface running speed is adjusted to 10 mm / s, the pulse energy output is adjusted to 18% (10.8 W), the repetition frequency is adjusted to 80 kHz, and the pulse width is adjusted to 0.1 ms.
[0104] Application Examples
[0105] 1. The porous membranes prepared in the above embodiments and comparative examples are prepared as solid electrolyte membranes. The specific preparation method includes the following steps:
[0106] 1) adding 50 parts by weight of solid electrolyte powder LATP, 0.5 parts by weight of thickener CMC, 0.25 parts by weight of dispersant BYK-156, 5 parts by weight of adhesive GR401, 0.1 parts by weight of wetting agent BYK-348, and 50 parts by weight of deionized water into a double planetary slurry kettle, stirring at 2000 rpm / min for 120 min to obtain a coating slurry;
[0107] 2) The coating slurry is applied to both sides of the porous membrane by a dip coating process to form a coating layer of 2.5 μm on both sides, and then dried at a temperature of 60° C. to 80° C. to obtain a solid electrolyte membrane.
[0108] 2. The solid electrolyte membrane prepared above is applied to a battery. The preparation of the battery includes the following steps:
[0109] 1) The positive electrode active material NCM811, the conductive agent SP, the conductive agent KS-6, and the binder PVDF were added to the solvent NMP in a mass ratio of 90:2:1:3, mixed evenly to form a positive electrode slurry, and coated on a 10 μm aluminum foil current collector; then dried in an oven at 95°C, and rolled on a roller press for use.
[0110] 2) Add artificial graphite, a negative electrode active material, acetylene black, a conductive agent, and CMC / SBR, a binder (mass ratio of 1:1), into water at a mass ratio of 90:5:5 and disperse evenly to form a negative electrode slurry, which is then coated on a copper foil current collector with a thickness of 10 μm, dried in an oven at 85° C., and rolled on a roller press for later use.
[0111] 3) In a drying room with a dew point of <-40°C, place the solid electrolyte composite membrane between the positive electrode sheet and the negative electrode sheet for stacking and packaging, and then heat it at 2.5g / m 2 The liquid is injected in a ratio of to obtain a battery.
[0112] Test Case
[0113] 1. The porous membranes prepared in the above embodiments and comparative examples all have circular straight through holes, and the outer periphery of the through holes has a convex portion, and the convex portion has a circular ring structure.
[0114] The porous membranes were tested for the following parameters:
[0115] 1. The ratio of the total projection area of the convex part on the membrane surface to the membrane area, and the ratio of the ring width of the convex part to the outer circle radius
[0116] Test method: Use a scanning electron microscope (e.g., a field emission scanning electron microscope) to take an image of the film surface after magnification. The observation magnification is adjusted according to the aperture. Remove the noise of the obtained image, use image analysis software to analyze the image, and calculate the ratio of the total projection area of the protrusion on the film surface to the film area, and the ratio of the ring width of the protrusion to the outer circle radius. Calculate the corresponding ratios of at least 9 protrusions observed in the field of view and take the average value.
[0117] 2. Ratio of the height of the single-sided protrusion to the film thickness
[0118] Test method: Use a scanning electron microscope (e.g., a field emission scanning electron microscope) to take an image of the film surface cross section after magnification. The observation magnification is adjusted according to the aperture. Remove the noise of the obtained image, use image analysis software to analyze the image, and thus calculate the ratio of the height of the single-sided protrusion to the film thickness. Calculate the corresponding ratio of at least 9 protrusions observed in the field of view and take the average value.
[0119] 3. Porosity
[0120] Test method: Refer to GB / T36363-2018 for testing.
[0121] 4. Aperture
[0122] Test method: Use a scanning electron microscope (e.g., field emission scanning electron microscope) to take a magnified image of the membrane surface. The observation magnification is adjusted according to the pore size. Remove the noise of the obtained image, use image analysis software to analyze the image, and the pore size can be calculated.
[0123] 5. Tensile strength
[0124] Test method: Test in accordance with GB / T 36363-2018.
[0125] 6. Puncture strength
[0126] Test method: Refer to GB / T36363-2018 for testing.
[0127] The above test results are shown in Table 1.
[0128] 2. The following parameters were tested on the solid electrolyte membranes prepared from the porous membranes of the above embodiments and comparative examples:
[0129] 1. Tensile strength
[0130] Test method: Test in accordance with GB / T 36363-2018.
[0131] 2. Puncture strength
[0132] Test method: Refer to GB / T36363-2018 for testing.
[0133] The above test results are shown in Table 1.
[0134] 3. The following parameters were tested on the batteries made of the porous membranes of the above embodiments and comparative examples:
[0135] 1. Battery energy density
[0136] Test method: Test the battery in the voltage range of 3.0V to 4.5V. Determine the discharge platform voltage by cyclic voltammetry at a rate of 0.5C, and then discharge at a constant current of 1C in a fully charged state to measure the discharge capacity. Calculate the mass energy density by the following formula:
[0137]
[0138] 2. Discharge DCIR, charge DCIR
[0139] Referring to the battery preparation method provided in the above application example, the solid electrolyte composite membrane is made into a soft-pack battery cell with a capacity of 5Ah. The testing equipment is Shenzhen Xinwei's CT-4008T-5V6A-S1 battery cell charging and discharging detection equipment and a constant temperature test chamber.
[0140] The specific steps are as follows:
[0141] 1) Through capacity calibration, the actual capacity of the soft-pack battery cell is measured to be 5Ah: in a constant temperature box at 25±2.5℃, the battery cell is put into sleep for 2 minutes, and the battery cell is discharged to 2.0V with a current of 1C (5A); after another 2 minutes of sleep, the battery is charged to 4.2V with a constant current and constant voltage of 1C current; finally, the above steps are repeated, and the capacity of the second discharge is calibrated as the actual capacity of the battery cell.
[0142] 2) Discharge DCIR test: Let the fully charged cell stand for 1 hour, use 1C current to discharge the cell to 50% SOC, then let it stand for 30 minutes, record the voltage V0 at this time as the OCV of 50% SOC; use 5C discharge current to discharge for 10 seconds, and record the voltage V1 at the 10th second; the discharge DCIR here can be calculated by the following formula:
[0143]
[0144] 3) Charging DCIR test: Let the discharged battery rest for 1 hour, charge the battery to 50% SOC with 1C current, and then let it rest for 30 minutes, and record the voltage V0 at this time as the OCV of 50% SOC; use a charging current of 3C to charge for 10 seconds, and record the voltage V1 at the 10th second; the charging DCIR here can be calculated by the following formula:
[0145]
[0146] Table 1
[0147]
[0148]
[0149] The following conclusions can be drawn from Table 1:
[0150] 1) By comparing Examples 1 to 10 and Comparative Examples 1, 2, and 3, it can be seen that when the ratio of the total projected area of the protrusions on the membrane surface to the membrane area is ≤80%, the porous membrane and the solid electrolyte membrane have higher tensile strength and puncture strength, and can be applied to the battery to make the battery have a higher energy density. The ratio of the total projected area of the protrusions on the membrane surface to the membrane area of Comparative Examples 1, 2, and 3 is too large, resulting in an excessively large pore size on the surface of the porous membrane, making the pore tortuosity of the solid electrolyte membrane relatively low and difficult to effectively play the role of isolating the positive and negative electrodes, resulting in a short circuit in the battery;
[0151] In addition, controlling the ratio of the total projected area of the protrusions on the membrane surface to the membrane area within the range of 18 to 70% is beneficial to balancing the improvement effect of the solid electrolyte loading on impedance and the disadvantages caused by the poor fit between the composite membrane and the electrode, thereby obtaining better impedance performance. When the above ratio exceeds 70%, due to the larger pore size, although the pore tortuosity is reduced, the poor fit leads to negative impedance performance. When the above ratio is lower than 18%, the proportion of the protrusions is low and the solid electrolyte loading is small. Although the fit with the electrode is good, the load has a greater impact on the impedance, showing slightly worse impedance performance.
[0152] 2) By comparing Example 1 and Example 2, it can be seen that in the preparation process of the porous membrane, the temperature of the base film surface is lowered to below 0°C in advance, and the ambient humidity in the laser drilling area is lowered to below the dew point temperature, so that the structure of the protrusion can be better controlled, and the ratio of the sum of the projected areas of the protrusions on the membrane surface to the membrane area, the ratio of the circular width of the protrusions to the outer circle radius, and the ratio of the height of the single-sided protrusions to the membrane thickness are all significantly smaller, the porosity and pore size of the porous membrane are also smaller, the tensile strength and puncture strength of the porous membrane and the solid electrolyte membrane are both superior, and the energy density of the battery cell is significantly higher. However, due to the significant increase in the proportion of the height of the protrusions in Example 2, the degree of fit between the porous membrane and the electrode is reduced, resulting in an increase in the interface impedance, which in turn leads to larger charging DCIR and discharge DCIR values of the battery.
[0153] 3) It can be seen from Examples 1, 5, 6, and 7 that, under the same preparation conditions, the protrusions of the porous membranes punched with different base membrane materials are well controlled, and all have excellent tensile strength and puncture strength. When applied to solid electrolyte membranes, the solid electrolyte membranes can also have excellent tensile strength and puncture strength, and when applied to batteries, the batteries can have excellent energy density.
[0154] 4) By comparing Examples 1, 3, 4, 8, 9, and 10, it can be seen that by regulating parameters such as the membrane surface running speed, pulse output energy, pulse repetition frequency, and pulse width during laser drilling, the structure of the protrusion can be adjusted, and the above parameters are controlled to meet the membrane surface running speed of 10 mm / s to 200 mm / s, the pulse output energy of 5.4 W to 9 W, the pulse repetition frequency of 8 kHz to 100 kHz, and the pulse width of 0.1 ms to 0.7 ms, all of which can make the total projection area of the protrusion on the membrane surface account for ≤80% of the membrane surface agent, thereby obtaining tensile strength, puncture strength, and battery cell energy density that are better than those of Comparative Examples 1 and 2. And by comparison, it can be seen that Examples 1, 3, and 4 satisfy the following conditions: the ratio of the total projection area of the protrusions on the membrane surface to the membrane area is ≤80%, the ratio of the annular width of the protrusions to the outer circle radius is ≤75%, the ratio of the height of the protrusions on one side to the membrane thickness is ≤50%, and the porosity is ≥12%. Although Examples 9 and 10 satisfy the following conditions: the ratio of the total projection area of the protrusions on the membrane surface to the membrane area is ≤80%, the ratio of the annular width of the protrusions to the outer circle radius is >75%, the ratio of the height of the protrusions on one side to the membrane thickness is >50%, and the porosity is ≥12%. The ratio of the height of the single-sided protrusion to the film thickness is greater than 50%, and the porosity is less than 12%; the ratio of the height of the single-sided protrusion to the film thickness of Example 9 is greater than 50%, and the porosity is less than 12%; the ratio of the height of the single-sided protrusion to the film thickness of Example 10 is greater than 50%, resulting in a poor mass energy density of the battery, and the tensile strength and puncture strength of the porous membrane and the solid electrolyte membrane are also worse at the same thickness. At the same time, the porous membrane of Example 10 has a larger pore size, which also leads to its battery impedance being too low, which will increase the risk of battery short circuit in practical applications;
[0155] By comparing Examples 8 and 9 with other examples, it can be seen that when the thickness of the porous membrane is too large, it will significantly affect the mass energy density and impedance of the battery, resulting in a significant decrease in the energy density of the battery cell and a significant increase in the discharge DCIR and charge DCIR.
[0156] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that the technical solutions described in the above embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A porous membrane formed by laser drilling, characterized in that: The porous membrane comprises a plurality of through holes and protrusions distributed on the periphery of the through holes, and the protrusions protrude from the membrane surface of the porous membrane; The ratio of the total projected area of the protrusions on the membrane surface of the porous membrane to the membrane surface area of the porous membrane is ≤80% and is not 0.
2. The porous membrane according to claim 1, characterized in that The ratio of the total projection area of the protrusions on the membrane surface of the porous membrane to the membrane surface area of the porous membrane is 18% to 70%.
3. The porous membrane according to claim 1 or 2, characterized in that The through hole is circular in shape, the projection of the protrusion on the surface of the porous membrane is a circular ring, and the ratio of the width of the circular ring to the outer circle radius is ≤75%.
4. The porous membrane according to any one of claims 1 to 3, characterized in that The ratio of the height of the protrusion to the thickness of the porous membrane is ≤50%; And / or, the porous membrane has a thickness of 5 μm to 20 μm.
5. The porous membrane according to any one of claims 1 to 4, characterized in that The porosity of the porous membrane is ≥12%, and the ratio of the total projected area of the protrusions on the membrane surface of the porous membrane to the membrane surface area of the porous membrane is ≤70%.
6. A method for preparing a porous membrane according to any one of claims 1 to 5, characterized in that: The following steps are involved: The base film is subjected to laser drilling treatment by using a laser drilling device to obtain the porous film; The laser drilling process meets the following conditions: the membrane surface running speed is 10 mm / s to 200 mm / s, the pulse output energy is 5.4 W to 9 W, the pulse repetition frequency is 8 kHz to 100 kHz, and the pulse width is 0.1 ms to 0.7 ms.
7. The preparation method according to claim 6, characterized in that: The laser drilling device is selected from a CO2 laser.
8. The preparation method according to claim 6 or 7, characterized in that: Before the laser drilling process is performed, the base film is cooled so that the temperature of the base film surface is ≤0°C; And / or, before performing the laser drilling process, the method further includes drying the environment in which the laser drilling device is located to reduce the humidity of the environment to below the dew point temperature.
9. An electrolyte membrane, characterized in that: The invention comprises the porous membrane according to any one of claims 1 to 5 and a solid electrolyte filled in the pores of the porous membrane.
10. A battery, characterized in that: Comprising the electrolyte membrane according to claim 9.
